Macromolecular synthesis in synchronized cultures of Anacystis nidulans. - Asato, Y (1979)
Synchronous culture of Anacystis nidulans has been induced by the light-dark-light regimen. At various time intervals during synchronous growth, samples were pulsed with radioactive labels to determine phospholipid, protein, ribonucleic acid (RNA), and deoxyribonucleic acid (DNA) syntheses within the cell division cycle. A temporal order of protein, RNA, and DNA syntheses occurred within the cell division cycle, whereas phospholipid was characteristically synthesized during midcycle (during cell enlargement) and during the time of cell division. Chemically determined protein, RNA, and DNA syntheses were found to support the schedule of these macromolecules in cultures growing at an 8-h doubling time.